The adjustment of degrees awarded by the Educational College of the Spanish National University for Distance Education (UNED) to the European Space of Higher Education - González Galán, María Ángeles (Avances en Supervisión Educativa, 2009)
The aim of this article is not to turn over the creation and development of the European Space for Higher Education, nor to analyse the suitability of the conclusions and guidelines adopted at international seminars by those countries that signed the Bologna Declaration, but to provide information on how the Spanish National University for Distance Education (UNED) has tried to give shape to these guidelines in its Degrees of Pedagogy and Social Education to be introduced shortly.
Keywords: UNED; european space of higher education; degree in pedagogy; degree of social education